ANCIENT GREEK ROOTS OF MODERN ADVOCATING FOR ANIMAL PROTECTION AND WELFARE - KALUĐEROVIĆ, Željko (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
The advocates of questioning the dominant anthropocentric view of the cosmos are becoming increasingly louder in raising (bio)ethical requirements for a new resolution of the relation between humans and other living beings, by claiming that the following of western philosophical and theological tradition has caused the present ecological, and not merely ecological crisis. Attempts are being made to establish a new relationship by relativizing the differences between man and non-human living beings often, by attributing specifically human properties and categories, such as dignity, moral status and rights, to non-human living beings. In this paper the author investigates the antecedents of the views deviating from the mainstream Western philosophy, in the sense of non-anthropocentric expansion of ethics, and finds them in the fragments of the first philosophers of nature, in which a kind of mixture of corporeal and psychical elements, i.e. the kinship of all varieties of life is emphasized. Pythagoras, Empedocles, Anaxagoras and Democritus, in this context, considered certain animals as sacred, i.e. they believed that animals are responsible for what they do and that they have a soul, intelligence, consciousness, ability to think, mind and reason. The author, finally, believed that the solution for the mentioned crisis does not lie in a simple levelling of animals upwards, i.e. in the attribution of similar or identical emotional and intellectual characteristics to all living beings, but in the adequate paideutic approach which shall develop in people an inherent bioethical model of accepting animals as being that deserve moral treatment, respect and adequate treatment. Protecția animalelor și starea de bine. Cei care își pun întrebări referitoare la percepția antropocentrică dominantă a cosmosului devin din ce în ce mai vocali în creșterea cerințelor (bio)etice pentru o nouă rezoluție a relației dintre ființele umane și alte viețuitoare, susținând că tradiția filosofică și teologică occidentală a cauzat prezenta criză ecologică, și nu pe cea doar ecologică. S-au făcut tentative pentru a stabili o nouă legătură prin relativizarea, de multe ori, a diferențelor dintre om și ființele non-umane, atribuindu-le acestora proprietăți și categorii specific umane, precum demnitatea, statutul moral și drepturile. În acest studiu, autorul investighează opiniile care deviază de la filosofia occidentală dominantă, în sensul expansiunii non-antropocentrice al eticii și le găsește fundamente în scrieri ale primilor filosofi ai naturii, unde se găsește un tip de mixtură de elemente corporale, i.e. rudenia tuturor formelor de viață. Pitagora, Empedocle, Anaxagora, și Democrit, în acest context, considerau anumite animale ca fiind sacre i.e. Ei credeau că animalele sunt responsabile pentru ceea ce fac și că au suflet, inteligență, conștiință, abilitatea de a gândi, minte și rațiune. Autorul, în final, crede că soluția pentru criza menționată nu rezidă doar dintr-o simplă reconsiderare a animalelor, i.e. prin atribuirea de caracteristici emoționale și intelectuale similare sau identice tuturor ființelor vii, ci din abordarea paideutică adecvată care ar trebui să dezvolte în oameni un model bioetic inerent al acceptării animalelor ca niște ființe ce merită un tratament moral, respect și comportamente adecvate. Cuvinte-cheie: antropocentrism, non-antropocentrism, anticipare, presocratici, om, animale, înrudire, responsabilitate, protecție, stare de bine